2021
DOI: 10.3390/socsci10060190
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Parental Mental Health and Child Maltreatment: The Importance of Family Characteristics

Abstract: The study expands the literature on parents’ mental health and risk of poor parenting by exploring the association between parental mental health diagnoses and types of child maltreatment among 522 parents who were adjudicated for child maltreatment by Israeli courts. The study was cross-sectional and used a manual for the content analysis of court cases. The results showed that 62% of the parents suffered from mental health problems, including emotional problems, personality disorders, mental illness or intel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Child maltreatment, including negative parenting behaviors, has been explored in extensive studies, and parental depression may be a risk factor for child maltreatment ( 32 ). David ( 33 ) found that 62% of parents who have maltreated their children had mental health problems (e.g., depression). Based on a longitudinal study with 1,813 families, Mustillo et al ( 34 ) reported that parental depression positively predicted child maltreatment in children aged 0 to 14.…”
Section: Parental Depression Internalizing and Externalizing Problems...mentioning
confidence: 99%
“…Child maltreatment, including negative parenting behaviors, has been explored in extensive studies, and parental depression may be a risk factor for child maltreatment ( 32 ). David ( 33 ) found that 62% of parents who have maltreated their children had mental health problems (e.g., depression). Based on a longitudinal study with 1,813 families, Mustillo et al ( 34 ) reported that parental depression positively predicted child maltreatment in children aged 0 to 14.…”
Section: Parental Depression Internalizing and Externalizing Problems...mentioning
confidence: 99%
“…It is in this context that it is important to develop family intervention programs in circumstances where they have not yet been developed and where they are most needed. This is particularly applicable to the difficult living conditions of families in developing countries, where poverty and violence are present in parenting, increasing the risk of child maltreatment (Beasley et al 2022;Ben David 2021;Etieyibo et al 2020;Gonzales 2017;Jiménez and Hidalgo 2016;Kotchick and Forehand 2002;Krug et al 2002;Long 2016;Maya and Hidalgo 2016;de Ossorno García et al 2017;Frías-Armenta et al 2017).…”
Section: Introductionmentioning
confidence: 99%